(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Infertility is a condition which could affect the entire world. This case study discusses a patient diagnosed with secondary infertility who had a history of one abortion after one year of unprotected sexual life and could not conceive subsequently after that. Considering the chances of abortion and the need for healthy uterus capable of childbirth, ayurvedic treatment plans were adopted. This case was diagnosed as Garbhasravi Vandhyata. Treatment plan included both Shodhana followed by Uthara vasthi and Shamana therapies. As a result of the Ayurvedic interventions made in three courses of treatment, the patient conceived and delivered a healthy baby boy.